Analysis of the Relationship of Drug Related Problems (DRPS) of Amlodipin Medicine Dosage Category on Geriatries' Blood Pressure Accomplishments - Retnowati Adiningsih; Truly Dian Anggraini; Elisabeth Septia Andini; Eliza Dian Hapsari (Indonesian Journal of Global Health Research, 2025)
The increase in the number of geriatrics leads to an increase in health problems, one of which is related to hypertension. Hypertension is an important risk factor for cardiovascular disease morbidity and mortality that is often found in geriatrics. The class of drugs that are widely used to reduce blood pressure and have the potential to cause DRPs is the Calcium channel blocker (CCB) class of drugs, namely amlodipine. Objective: The purpose of this study was to analyze the relationship of Drug related problems (DRPs) in the single dose category in the use of amlodipine drugs to the achievement of geriatric blood pressure targets. Method: This study is a descriptive study using a cross-sectional observational design that is analytic in nature. Sampling using purposive sampling technique. The data analysis used was univariate and bivariate analysis. Result: The results showed that 70% of patients were female, 40% were over 70 years old and 70% of patients had stage 2 hypertension. There was 1 patient who experienced drug related problems (DRPs) in the drug dosage category with the result that the blood pressure target was not achieved and 1 patient who received the right dose of amlodipine with the result that the blood pressure target was not achieved. Conclusion: From the results of the study it can be concluded that there is no significant relationship between Drug Related Problems (DRPs) in the category of amlodipine drug dosage with the achievement of geriatric blood pressure targets (p = 0.35).